Impaired Sensory Processing During Low-Oxygen Exposure: A Noninvasive Approach to Detecting Changes in Cognitive States - Seech, Todd R.; Funke, Matthew E.; Sharp, Richard F.; Light, Gregory A.; Blacker, Kara J. (Frontiers in Psychiatry, 2020)
The ability to detect novelty in our environment is a critical sensory function. A reliable set of event-related potentials (ERP), known as the auditory deviance response (ADR), are elicited in the absence of directed attention and indexes functionally relevant networks. The ADR consists of three peaks: mismatch negativity (MMN), P3a, and reorienting negativity (RON) that are sequentially evoked in response to unattended changes in repetitive background stimulation. While previous studies have established the ADR’s sensitivity to a range of pharmacologic and non-pharmacologic interventions and are leading candidate biomarkers of perturbations of the central nervous system (CNS), here we sought to determine if ADR peaks are sensitive to decreases in breathable oxygen. Participants performed a visuomotor tracking task while EEG was recorded during two 27 minute sessions. The two sessions differed in the amount of environmental oxygen available: 10.6% O2 (hypoxia) versus 20.4% O2 (normoxia). ERPs were measured while a series of identical, or “standard,” tones combined with occasional “oddball,” tones, were presented. MMN, P3a, and RON were assessed in response to the oddball compared to the standard stimuli. Behavioral impairment during hypoxia was demonstrated by a deficit in tracking performance compared to the normoxia condition. Whereas no changes were detected in the MMN or RON, the amplitude of the P3a component was significantly reduced during hypoxia compared to normoxia, within the first 9 minutes of exposure. To our knowledge, this is the first study to demonstrate the effect of low oxygen exposure on passively elicited neural measures of early sensory processing. This study demonstrates that passively elicited EEG measures, reflecting pre-attentive auditory processing, are disrupted by acute hypoxia. Results have implications for the development of biomarkers for the non-invasive assessment of CNS perturbations.